Copper-catalyzed synthesis of indolyl diketones via C–H oxidation/diacylation of indoles with arylglyoxal hydrates. Issue 29 (11th July 2017) - Wang, Cuiping; Zhang, Zhiqiang; Liu, Kui; Yan, Jingbo; Zhang, Tiexin; Lu, Gonghao; Meng, Qingtao; Chi, Haijun; Duan, Chunying
Abstract : Copper-catalyzed synthesis of indolyl diketones via C–H oxidation/diacylation of indoles with arylglyoxal hydrates is described. Abstract : An expedient protocol for Cu-catalyzed C–H oxidation/diacylation of indoles with arylglyoxal hydrates to construct indolyl diketones is developed. This methodology exhibits the synthetic utility of the synthesis of an indole-alkaloid 1, 2-di(1 H -indol-3-yl)ethane-1, 2-dione and offers a straightforward means to produce different indolyl nitrogen-containing heterocycles such as indolyl quinoxaline, indolyl hydantoin and indolyl imidazole in high yields. Preliminary mechanistic studies indicate that two proposed pathways are involved in this process.